FRI0667 IS OBESITY A FACTOR OF POOR OUTCOME IN SPONDYLOARTHRITIS? AN ANALYSIS OF 638 PATIENTS. (June 2019) - Claudepierre, Pascal; Gossec, Laure; Grange, Laurent; Garrido-Cumbrera, Marco; Desfleurs, Emilie; Launois, Francoise Alliot; Flipo, René-Marc
Abstract : Background: There are few data on obese patients with axial spondyloarthritis (axSpA). Objectives: To explore the impact of body mass index (BMI) on personal, professional and social life of axSpA patients. Methods: BetweenDecember 2017 and February 2018, French patients followed for axSpA by their rheumatologists or affiliated to the French patients association AFLAR, and self-reporting axSpA, participated in the European Map of Axial Spondyloarthritis (EMAS) cross-sectional patient survey 1 . Sociodemographic data (including weight and height), axSpA characteristics and disease impact on personal (social interactions, frequency of social activities) and professional life (working hours, sick leave, and disability) were collected via an online questionnaire. Patients were classified in two groups according to their BMI (obese BMI≥30 kg/m 2, non-obese: BMI<30 kg/m 2 ) and a comparison between the two groups was conducted using chi2 or Mann-Whitney tests. There was no imputation of missing data. Results: Data of 638 patients, mainly women 77%, median age (years) 41.5±11.1 were collected in France in 2018. Median BMI was 26.1±5.5 and 22.1% patients were obese (n=141). Median age was significantly higher in obese patients (44.1±9.9 vs 40.8±11.3; p=0.001), but there was no difference regarding gender, level of education and socio-professional categories. The obese had a longer diagnosis delay for axSPA (median 8.2±8.4 vs 6.6±8.1 years; p=0.01). They were more to report psoriasis (33.8% vs 21.9%; p=0, 005) and the following comorbidities: anxiety, depression fibromyalgia, high blood pressure, hypercholesterolemia, diabetes and renal failure. Disease activity was also higher in the obese population: median BASDAI 6.5±1.5 vs 5.8±1.8 (p<0.001) and BASDAI ≥ 4 in 92.9% vs 84.3% (p<0.01). The same proportion of patients (61.9%) has been treated by a biologic in the two groups. The impact of axSPA on personal life was more frequently reported by the obeses: 65.2% vs 48.0% (p<0.005) had reduced the frequency of sport activities because of axSpA and 42.5% vs 28.3% (p<0.005) their sexual intercourse. There were a lower number of obeses, who had a regular physical activity (58.9% vs 68.8%; p>0.05) with a shorter mean duration of sport practice. At the opposite, no difference was observed regarding the impact of axSpA on professional life, with a similar proportion of obese and non-obese patients reporting sick leave (32.1% vs 24.9%) or disability (31.9% vs 28%). The mean number of working hours for the active people was also similar (35.5 vs 34.2 hours) in the two groups. Conclusion: In this survey, obesity affected 22.1% of axSpA patients and was associated to a higher disease activity and a greater impact on personal life of axSpA, but not on their professional life. Obesity and its consequences have to be considered in the management of axSpA as it is already the case for psoriatic arthritis. References: [1] Gossec, et al. Diagnostic Delay and Associated Factors in Axial Spondyloarthritis across Europe. Results from the European Map of Axial Spondyloarthritis Survey. Arthritis Rheumatol. 2018 Sep;70Suppl 9:688 Acknowledgement: Survey supported by Novartis Disclosure of Interests: Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, Laure Gossec Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis-Sandoz, Pfizer, Sanofi, and UCB, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Nordic Pharma, Novartis-Sandoz, Pfizer, Roche, Sanofi, and UCB, Consultant for: L Gossec has received honoraria from Celgene as investigator for this study, LAURENT GRANGE Consultant for: Laurent Grange has received honoraria from Amgen, Lilly and UCB and research support from Lilly, Amgen, UCB, Expanscience, Mylan, Roche diagnostics and TEVA, Marco Garrido-Cumbrera Consultant for: Honoraria from Novartis as steering committe of this survey, Emilie Desfleurs Employee of: Employee of Novartis Pharma, Francoise Alliot Launois: None declared, René-Marc Flipo Consultant for: Honoraria from Novartis as steering committe of this survey